DIVORCE IN KANGEAN ISLANDS: The Study on Judge's Legal Reasoning of Kangean Religious Court, 2020-2022 - Syaifuddin Zuhdi; Khudzaifah Dimyati; Absori Absori; Kelik Wardiono; Filzah Ilda Syafirah (Universitas Muhammadiyah Surakarta, 2022)
Purpose of the study: This article aims to find out how the divorce conditions in the Kangean Islands are and to see how the factors that influence it and the legal reasoning used by the judge in deciding the divorce case. Methods: the method used in this study is a normative juridical method with a decision approach, the data used is secondary data, namely the decisions of the religious courts in 2020-2022, which every year 30% of the decisions are taken, the data are analyzed descriptively Results: From the research conducted, it was found that the majority of divorces in Kangean Island were carried out by a contested divorce mechanism, while the factors behind the majority were due to disputes, then followed by economic factors, legal reasoning judges were divided into empathy, namely the use of legal norms, conformity between facts and norms. , interpretation of problems and norms, as well as the use of the rules of Islamic law in its legal opinion Applications of this study: This article is useful to support research on divorce and legal opinions, especially on Kangean Island and Indonesia in general Novelty: The novelty of this research is that there are still very few people doing research on the Kangean Islands, as well as the discovery of several legal reasoning concepts for judges at the Kangean Religious Court. ABSTRAK Tujuan Penelitian: Artikel ini bertujuan untuk mengetahui bagaimana kondisi perceraian di Kepulauan Kangean dan melihat bagaimana faktor-faktor yang mempengaruhinya serta alasan hukum yang digunakan hakim dalam memutus perkara perceraian. Metode : Metode yang digunakan dalam penelitian ini adalah metode yuridis normatif dengan pendekatan putusan, data yang digunakan adalah data sekunder yaitu putusan pengadilan agama tahun 2020-2022 yang setiap tahun diambil 30% putusannya, data tersebut dianalisis secara deskriptif Hasil: Dari penelitian yang dilakukan diketahui bahwa mayoritas perceraian di Pulau Kangean dilakukan dengan mekanisme cerai gugat, sedangkan faktor penyebab mayoritas adalah karena perselisihan, kemudian disusul faktor ekonomi, pertimbangan hukum hakim terbagi menjadi empati, yaitu penggunaan norma hukum, kesesuaian antara fakta dan norma. , interpretasi masalah dan norma, serta penggunaan aturan hukum Islam dalam opini hukumnya Aplikasi penelitian ini: Artikel ini bermanfaat untuk mendukung penelitian tentang perceraian dan opini hukum khususnya di Pulau Kangean dan Indonesia pada umumnya Kebaruan: Kebaruan dari penelitian ini adalah masih sedikitnya orang yang melakukan penelitian di Kepulauan Kangean, serta ditemukannya beberapa konsep penalaran hukum bagi hakim di Pengadilan Agama Kangean.